Experimental Study of the Tensile Strength and Energy Characteristics of Sandstone with Different Moisture Contents - LIAO Anjie; LAI Lin (Renmin Zhujiang)
In order to study the influence of the tensile strength and energy characteristics of sandstone with different moisture contents,this paper tests the tensile strength of sandstone with different moisture contents by the rock test press.The results show that:①The tensile strength of sandstone decreases with the increase of the moisture content.Water softens rocks,resulting in the deterioration of the mechanical properties of sandstone,thus reducing the tensile strength of sandstone.②The total energy and elastic strain energy of sandstone decrease,while the dissipation energy increases with the increase of the moisture content.There is energy accumulation before the energy cut-off point,and then the energy dissipation in sandstone.③With the increase of water content,the ratio of elastic strain energy to total energy of sandstone decreases,and the water content in rock cracks increases.Under the action of load,pore water pressure will cause stress concentration,resulting in the expansion of rock micro-cracks,the increase of dissipation energy,and the increased ratio of dissipation energy to total energy.